Forecasting methods of non-stationary stochastic processes that use external criteria - Kononenko, Igor; Ryepin, Anton (My University, 2008)
The purpose of this work is to create and study an effective forecasting method of non-stationary stochastic processes in the case when observations in the base period are scarce.
Keywords: forecasting problems; H-criterion method; estimation of parameters; stochastic processes; forecasting